Parenting styles and aggressive behaviors in adolescents from a public educational institution, Juliaca - Larico Viamonte, Rocina (2023)
Objective: to determine the relationship between parenting styles and the level of aggressive behavior in adolescents from a public educational institution, Juliaca, 2022. Methodology: qualitative approach of correlational level, non-experimental design. On the other hand, the population was 796 subjects of both sexes from 14 to 17 years of age that represent a non-probabilistic type of convenience sample. The instruments used were the "Parenting Styles Scale" prepared by Lawrence Steinberg 1991 and adapted in Peru by Merino and Arndt (2004) and the Aggression Questionnaire (AQ) prepared by Arnold H. Buss and Mark Perry in 1992 in the United States and adapted in Peru by Matalinares      in 2012. Results: at the conclusion of this investigation, it was found in the results that there is a significant relationship where the significance level is 0.000. Conclusion: there is a direct relationship between both variables.